2022
DOI: 10.1177/21582440221079638
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Integration of Psychological and Socio-cultural Factors in Adjustment of Expatriates: An AUM Process Model

Abstract: While the literature develops an adequate understanding of various socio-cultural and psychological factors that contribute to expatriates’ adjustment, limited work exists regarding interdependencies between these two dimensions of adjustment, particularly in the Asian context. Using the theoretical lens of the anxiety uncertainty management (AUM) model, this research examined the various socio-cultural and psychological factors that affect expatriates’ adjustment, and the integration of these factors during a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 94 publications
(143 reference statements)
0
8
0
Order By: Relevance
“…SIEs are recognised as (a) talented individuals, (b) who self-initiate their international assignments, (c) who have regular employment intentions and (d) who intend to stay temporarily in the host country (Cerdin and Selmer, 2014). The skills and knowledge of these expatriates are key assets that help firms to develop a competitive advantage in a context characterised by skill shortages and war over talent (Berraies, 2019).The performance of expatriates is still a topic of debate in the international business literature (Lauring and Selmer, 2018;Mumtaz and Nadeem, 2022;Jannesari and Sullivan, 2021;Amari, 2022;Nolan and Liang, 2022). Nevertheless, little is known about how SIEs cohort contributes to the performance of host country organisations (Mumtaz and Nadeem, 2022;Koveshnikov et al, 2022, Swalhi et al, 2023.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…SIEs are recognised as (a) talented individuals, (b) who self-initiate their international assignments, (c) who have regular employment intentions and (d) who intend to stay temporarily in the host country (Cerdin and Selmer, 2014). The skills and knowledge of these expatriates are key assets that help firms to develop a competitive advantage in a context characterised by skill shortages and war over talent (Berraies, 2019).The performance of expatriates is still a topic of debate in the international business literature (Lauring and Selmer, 2018;Mumtaz and Nadeem, 2022;Jannesari and Sullivan, 2021;Amari, 2022;Nolan and Liang, 2022). Nevertheless, little is known about how SIEs cohort contributes to the performance of host country organisations (Mumtaz and Nadeem, 2022;Koveshnikov et al, 2022, Swalhi et al, 2023.…”
Section: Introductionmentioning
confidence: 99%
“…The skills and knowledge of these expatriates are key assets that help firms to develop a competitive advantage in a context characterised by skill shortages and war over talent (Berraies, 2019).The performance of expatriates is still a topic of debate in the international business literature (Lauring and Selmer, 2018;Mumtaz and Nadeem, 2022;Jannesari and Sullivan, 2021;Amari, 2022;Nolan and Liang, 2022). Nevertheless, little is known about how SIEs cohort contributes to the performance of host country organisations (Mumtaz and Nadeem, 2022;Koveshnikov et al, 2022, Swalhi et al, 2023. Therefore, a deeper understanding of the factors determining creativity within host organisations and the potential mechanisms through which creativity can be enhanced, is necessary.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, some literature indicates that prior work experiences, particularly foreign experiences, facilitate individuals in dealing with complex and ambiguous situations, as working in foreign countries promotes the development of new competencies and flexible approaches in employees (Myers & Pringle, 2005). Moreover, previous experience provides a diverse array of knowledge and skill sets to employees which can be drawn upon in unexpected situations for quickly dealing with uncertainties and new challenges (Mumtaz & Nadeem, 2022). Foreign work experiences are likely to be particularly useful in broadening female executives' horizons and enabling them to respond flexibly to unexpected situations.…”
Section: High Adaptabilitymentioning
confidence: 99%
“…Assignments are often characterized by so called expatriate crises that can evolve at micro (personal and family), meso (network and organisational domains) and macro (host country) levels. (McNulty et al, 2019) Expatriate adjustment is a dynamic, psychologically and contextually determined process (Banai, 2022;Mumtaz & Nadeem, 2022) and, constitutes a challenge to individuals paradoxically even in a culturally similar country (Vromans et al, 2013) It has been revealed that the most significant factors driving expatriate success are the following: cross-cultural competences, spousal support, motivational questions, time of assignment, emotional competences, previous international experience language fluency, social relational skills, cultural differences, and organizational recruitment and selection practices (Canhilal & Shemueli, 2015). In their review DeNisi and Sonesh (2016) propose a multidimensional model of success and failure in international assignments.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This is because the greater the difference between the cultural characteristics of a country and the organizational culture operating in it, the greater the challenge for management in bridging them. (Borgulya, 2014;Meier, 2002;Tahir & Egleston, 2019;Singh et al, 2019) The international organizations can be successful in such a cultural environment if they develop in their own organizational culture the ability for cultural sensitivity among their employees based on understanding and empathy (Holt & Wiggington, 2002;Setti et al, 2020;Mumtaz & Nadeem, 2022). This flexible behaviour allows them to adapt effectively to the unique cultural environment and to manage cultural differences accordingly (Deresky, 2014) both between the "headquarter" of multinational corporation and its subsidiaries and between the employees, especially expatriates.…”
Section: Introductionmentioning
confidence: 99%